2020
DOI: 10.1016/j.fsigen.2019.102187
|View full text |Cite
|
Sign up to set email alerts
|

Expediting the sampling, decalcification, and forensic DNA analysis of large elephant ivory seizures to aid investigations and prosecutions

Abstract: A B S T R A C TThe illegal ivory trade continues to drive elephant poaching. Large ivory seizures in Africa and Asia are still commonplace. Wildlife forensics is recognised as a key enforcement tool to combat this trade. However, the time and resources required to effectively test large ivory seizures is often prohibitive. This limits or delays testing, which may impede investigations and/or prosecutions. Typically, DNA analysis of an ivory seizure involves pairing and sorting the tusks, sampling the tusks, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…A few communications by wildlife forensic investigators (e.g., the US Fish & Wildlife Service Forensics Laboratory) used DNA extracted from recent ivory carvings or idols to identify elephant species (Gupta et al, 2011). Recently, Ewart et al (2020) optimized DNA extraction protocols on both raw and worked elephant ivory and demonstrated that powdering the ivory directly with a drill, as well as short decalcification times (2 h), produces results comparable with sample powdering in liquid nitrogen and a longer decalcification time (3 days). In addition, sampling the cementum and using a total demineralisation DNA extraction method contribute to minimizing the amount of elephant ivory that is necessary in order to recover DNA (Winters et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A few communications by wildlife forensic investigators (e.g., the US Fish & Wildlife Service Forensics Laboratory) used DNA extracted from recent ivory carvings or idols to identify elephant species (Gupta et al, 2011). Recently, Ewart et al (2020) optimized DNA extraction protocols on both raw and worked elephant ivory and demonstrated that powdering the ivory directly with a drill, as well as short decalcification times (2 h), produces results comparable with sample powdering in liquid nitrogen and a longer decalcification time (3 days). In addition, sampling the cementum and using a total demineralisation DNA extraction method contribute to minimizing the amount of elephant ivory that is necessary in order to recover DNA (Winters et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The high success rate (97%) of this M-HRM assay can most likely be explained by (1) the use of a sanding technique for obtaining ivory powder, (2) small amplicon sizes, and (3) the use of an annealing temperature gradient. Sanding ivory into a fine powder, like cutting [14] or drilling ivory, then pulverizing the ivory in liquid nitrogen [6], increases the surface area available to react with EDTA during the overnight demineralization step [21]. EDTA decalcifies the ivory by chelating the metal ions, such as calcium (Ca 2+ ).…”
Section: Discussionmentioning
confidence: 99%
“…We collected genetic samples from 166 casques. We used a Dremel drill to collect 1.8–2.0 mg of powdered material per casque (Ewart et al ., 2020). Dried facial/gular skin was sampled where available using a sterile scalpel to cut approximately 1.5 × 1.5 × 3 mm (Mundy, Unitt, & Woodruff, 1997).…”
Section: Methodsmentioning
confidence: 99%